Silicon Nanoparticles Enhance Ginger Rhizomes Tolerance to Postharvest Deterioration and Resistance to Fusarium solani - Peng, Huimin; Hu, Haijun; Xi, Keyong; Zhu, Xiongmeng; Zhou, Jie; Yin, Junliang; Guo, Fengling; Liu, Yiqing; Zhu, Yongxing (Frontiers in Plant Science, 2022)
Postharvest deterioration of ginger rhizome caused by microorganisms or wound infections causes significant economic losses. Fusarium solani is one of the important causal agents of prevalent ginger disease soft rot across the world. The massive and continuous use of chemical fungicides in postharvest preservation pose risks to human health and produce environmental contamination. Hence, new alternative tools are required to reduction of postharvest physiological deterioration and extension of the postharvest life of ginger. In this study, the use of silicon nanoparticles (SiNPs) on the storability of ginger rhizomes during postharvest storage and their resistance to Fusarium solani were investigated. The results showed that 50, 100, and 150 mg L-1 of SiNPs increased the firmness of the ginger rhizome during storage, but decreased the decay severity, water loss, total color difference, and the reactive oxygen species (ROS) (H2O2 and superoxide anion) accumulation. Specifically, 100 mg L-1 (SiNP100) demonstrated the best effect in the extension of postharvest life and improved the quality of the ginger rhizomes. SiNP100 application increased the activities of antioxidant enzymes (superoxide dismutase [SOD] and catalase [CAT]) and the total phenolics and flavonoid contents, thereby reducing the ROS accumulation and malondialdehyde (MDA) content. Meanwhile, SiNP100 treatment negatively impacts the peroxidase (POD) and polyphenol oxidase (PPO) activities, which may have contributed to the lower level of lignin and decreased total color difference. SiNP100 likely decreased water loss and the transfer of water by altering the expression of aquaporin genes. Moreover, SiNP100 modulated the expression of lignin synthesis and phytopathogenic responses genes including MYB and LysM genes. Furthermore, SiNP100 inhibited Fusarium solani by preventing the penetration of hyphae into cells, thus decreasing the severity of postharvest pathogenic decay. In summary, this study provides a foundation for using SiNP100 resources to maintain ginger quality and control postharvest diseases.